2019
DOI: 10.1016/j.cell.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Activated PMN Exosomes: Pathogenic Entities Causing Matrix Destruction and Disease in the Lung

Abstract: Here, we describe a novel pathogenic entity, the activated PMN (polymorphonuclear leukocyte, i.e., neutrophil)-derived exosome. These CD63 + /CD66b + nanovesicles acquire surface-bound neutrophil elastase (NE) during PMN degranulation, NE being oriented in a configuration resistant to a1-antitrypsin (a1AT). These exosomes bind and degrade extracellular matrix (ECM) via the integrin Mac-1 and NE, respectively, causing the hallmarks of chronic obstructive pulmonary disease (COPD). Due to both ECM targeting and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
313
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(330 citation statements)
references
References 53 publications
12
313
0
5
Order By: Relevance
“…In pathological states, dysregulation of EV cargo can have profound effects in disease by fundamentally altering the microenvironment and cellular phenotypes through disruption of normal homeostatic pathways while augmenting pathological signals. To this end, several studies reported EVs having a functional role in pulmonary diseases, such as acute lung injury, chronic obstructive pulmonary disease, and lung cancer (25)(26)(27)(28)(29)(30)(31). Only recently have studies begun unraveling the role that EVs play in mediating fibroproliferation (32)(33)(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
“…In pathological states, dysregulation of EV cargo can have profound effects in disease by fundamentally altering the microenvironment and cellular phenotypes through disruption of normal homeostatic pathways while augmenting pathological signals. To this end, several studies reported EVs having a functional role in pulmonary diseases, such as acute lung injury, chronic obstructive pulmonary disease, and lung cancer (25)(26)(27)(28)(29)(30)(31). Only recently have studies begun unraveling the role that EVs play in mediating fibroproliferation (32)(33)(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, neutrophil EV-associated effector functions are also known to contribute to innate immune pathology. For example, the surface-bound neutrophil elastase of EVs has been shown to cause extracellular matrix destruction and disease in the lungs of COPD patients and could help explain the antifungal activity of afEVs (57).…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows for the first time that the plasma membrane undergoes dramatic changes during NETosis, including shedding of microvesicles and regulated permeabilization. The shedding of microvesicles is of particular interest, as they could be important systemic messengers, providing activated neutrophils undergoing NETosis with additional ways of signaling stress (52) or contributing to disease (53). For instance, microvesicles are procoagulant, thus could potentially contribute to the pro-thrombotic activity of NETs (54).…”
Section: Discussionmentioning
confidence: 99%